Implementation of OBE in a MoT course: lesson learned - Shamsuddin, Alina; Wahab, Eta; Abdullah, Nor Hazana; Chan, Chee-Ming (American Scientific Publishers, 2018)
There is a growing concern among practitioners on the competencies of fresh graduates in Malaysia. Some of the organizations have developed ‘special’ trainings to equip our graduates who are perceived as lack of soft skills and not ready to join the workforce. The Education Ministry has even developed a BLUEPRINT on our graduates attributes that needed by the industries. Outcome Based Education (OBE) has been introduced and implemented for more than 5 years in Malaysia. However, the program learning outcomes (PLOs) that supposedly converted into competencies and attributes of graduates have failed to satisfy the industries. Hence, this paper explores the issues and challenges in implementing OBE in a course in a management of Technology (MoT) program in UTHM. It adopts the qualitative methodology. The research strategy is a case study. The case study protocol is based on the stages in OBE implementation. The findings discovered that there are three critical issues that hinder the success of the implementation of the OBE concepts; which are at least the human capital factor (lecturers and students), the system (management) and the infrastructure (e.g., library, classroom, etc.) that related to OBE implementation.